Perlindungan Hak Asasi Manusia dalam sistem ketatanegaraan Indonesia - Andi Aco Agus (Jurnal Ekonomi dan Riset Pembangunan, 2026)
This study aims to determine the Indonesian constitutional system guarantees the protection of Human Rights (HAM), the institutions and mechanisms that play a role in protecting Human Rights (HAM) in Indonesia, and the challenges and obstacles in implementing Human Rights protection (HAM) in Indonesia. The research method used is descriptive research with library research. Research activities are carried out by collecting information and data with the help of various existing materials. The results of the study indicate that the protection of Human Rights (HAM) in the Indonesian constitutional system is an inseparable part of the legal and governmental structure of the country. Guarantees for Human Rights are not only moral or philosophical, but have been constitutionally affirmed through the 1945 Constitution of the Republic of Indonesia, especially after the amendment that included Chapter XA which contains various fundamental rights of every individual. This emphasizes the state's obligation to respect, protect, uphold, and advance Human Rights in all aspects of life.